Pituicytoma. Case report and literature review (2018)
Pituicytoma is a rare glial tumour located in the sellar and/or suprasellar region of the brain, it originates from pituicytes, and they were included in the World Health Organization (WHO) Classification of Central Nervous System Tumours in 2017. As mentioned above it originates from pituicytes cells in the posterior pituitary near the infundibulum. Histological characteristics permits classification and identification among other central nervous system tumours localized in the posterior pituitary or infundibulum. WHO classification describes them as grades such as grade I tumour which has a differentiated structure composed of spindle-shaped cells presumably derived from pituicytes. We report the case of a 37-year-old woman who developed a suprasellar tumour and that it was discovered following a past medical history of amenorrhoea and migraines. Once the lesion was detected in images, the patient rejected surgical treatment even when she developed galactorrhea and preferred medical treatment with cabergoline. However, two years later she developed visual defects due to increase in size by that time accepting surgical treatment. A review of the literature including most common clinical and radiological features of this entity as well as treatment protocols proposed are discussed.